Development of Efficiency in Public Services of Local Administrative Organizations to Enhance the Level of Sufficiency Economy in the Northern Region of Thailand - Nonthakhot, Phanin; Somyana, Pattarawut (Journal of Applied Economics and Management Strategy, 2024)
The purposes of the research were to investigate the factors affecting Sufficiency Economy Philosophy (SEP), and enable the ways to improve farmers’ livelihoods based on SEP. The participatory research with 30 subdistrict administrative organizations was carried out by speculative random sampling organizations in Chiang Mai, Lamphun, Chiang Rai, Payao, Uttaradit, and Nan. Each subdistrict administrative organization selected 300 farmers for the project. The smart SEP farmers were tested for measuring the level of Sufficiency Economy, and then analyzed the efficiency of agricultural public services of the subdistrict administrative organization using the Data Envelopment Analysis Program (DEAP). The research results revealed that all subdistrict administrative organizations had high-efficiency management that affected the drive to improve the farmers’ livelihoods based on the SEP. On the efficiency values in agricultural public service, the average score was 88.30 percent. The factors affecting the efficiency of agricultural public service of the subdistrict administrative organizations were: (1) the proportion of agricultural budget to the local budget (2) full-time employees in charge of agriculture and (3) number of agricultural learning centers. Moreover, it was found that the subdistrict administrative organization with high efficiency could upgrade the level of smart SEP farmers at the accessible level as well. In addition, farmers were able to raise their livelihoods higher, from not being in the category, and access to being smart SEP farmers. However, there are some suggestions that the subdistrict administrative organizations should plan to drive and upgrade to higher efficiency by establishing a Sufficiency Economy project in agriculture. That affects to increase the livelihoods of farmers by having sufficient budget and personnel responsible and integrating work with researchers. Thai should be stated in the budget plan for each year and the 5-year strategic planning of the subdistrict administrative organizations to ensure sustainability.